Correlation between Antioxidant Activity and the Garcinol Content Released from Fruit Rinds of Endemic Garcinia quaesita Pierre on Different Cooking Conditions - Donisha Shani Niharika Keembiya Liyanagamage; Susanthi Jayasinghe; Anoja Priyadarshani Attanayake; Veranja Karunaratne (Journal of Food Quality)
The antioxidant activity of garcinol has been identified as the basis for various bioactivities in it, and the genus Garcinia is the main source for the garcinol. G. quaesita, which is endemic to Sri Lanka, is a representative member of genus Garcinia, and the dried fruit rind of G. quaesita is used practically in all curry preparations to impart a sour flavor. In our study, garcinol was isolated (yield: 3.67%) from the dried fruit rind of G. quaesita, for the first time. Further, how cooking conditions enable the ingestion of garcinol during the consumption of curries was also examined. The garcinol content released in different cooking conditions was positively correlated with the antioxidant activity in vitro. The results revealed that boiling virgin coconut oil extract of G. quaesita, simulating the common practice of oil frying during cooking, is the best method for obtaining the highest amount of garcinol into the curry medium.